An urgent need to review the approach to a febrile child in the COVID-19 era? - D'Souza, Rashmi S.; Freitas, Joana; Rainsley, Victoria; Mason, Felix; Kenny, Julia; Thomas, Jessica (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2020)
Background: There have been reports of a new hyperinflammatory syndrome in children defined as the Paediatric Inflammatory Multisystem Syndrome temporally associated with COVID-19 (PIMS-TS). Our hospital has experienced a great proportion of children attending an Emergency Department (ED) with possible PIMS-TS so far reported in the UK. Objectives: We describe the clinical and biochemical findings in children with possible PIMS-TS in the context of a local ED. Settings: Queen Elizabeth Hospital (QEH), Woolwich, a District General Hospital (DGH) in South London. Participants: From 14th March to 18th May 2020, children presenting to QEH and transferred to tertiary care for possible PIMS-TS, with a history of fever and hyperinflammatory symptoms, raised inflammatory markers and without a clear clinical or microbial cause were identified. Demographic data, clinical and laboratory data were recorded as median [range]. Results: 17 children (12 male) were identified aged 11 [1-16] years. 17/17 had a fever; other common symptoms were conjunctival injection, rash and gastrointestinal symptoms. Lymphopenia and raised inflammatory markers were evident. 15/17 were tested with nasopharyngeal and oropharyngeal SARS-CoV-2 PCR swabs and 15/15 were negative. Before transfer, one child required intubation and four required inotropes. All children were transferred to a tertiary unit, 10 within the first 24 hours. After transfer, 2/17 had microbial causes evident on urine/stool culture. Conclusions: PIMS-TS is proving challenging to diagnose in a DGH ED because of heterogeneity of symptoms and laboratory markers, overlapping with other diseases, and cardiac complications despite deceptively benign presentations. There is an urgent need to review the approach to a febrile child in this setting, to optimise identification of PIMS-TS. Prognostic markers and risk stratification methods would help paediatricians working in the ED and general paediatric wards.